2022
DOI: 10.3390/nano12111885
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Extract-Mediated Fabrication of Photosensitive Aluminum Oxide Nanoparticle and Their Antioxidant and Anti-Inflammatory Potential

Abstract: Aluminum oxide nanoparticles (Al2O3 NPs) were synthesized using a simple, eco-friendly green synthesis approach in an alkaline medium from the extract of grapefruit peel waste. The pre-synthesized, nano-crystalline Al2O3 NPs were characterized by using spectroscopic (UV–vis, FTIR, XRD, and EDX) and microscopic (SEM and TEM) techniques. The formed Al2O3 NPs exhibited a pronounced absorption peak at 278 nm in the UV–vis spectrum. The average particle size of the as-prepared Al2O3 NPs was evaluated to be 57.34 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Antioxidant conjugation of AlNPs can improve their stability and enhance their therapeutic efficacy. Various Al-based NPs exhibited potential antioxidant activity, such as grapefruit peel-fabricated Al 2 O 3 NPs [253], Irganox 1010-fabricated Al 2 O 3 -poly(ethyleneco-butyl acrylate) nanocomposites [254], and Al 2 O 3 NPs synthesized via the laser ablation technique [255]. The conjugation of antioxidants with NPs or entrapped in nanogel can also enhance their bioavailability and facilitate their cellular uptake, in addition to diminishing free radicals [256].…”
Section: Aluminum-based Nps (Alnps) and Their Antioxidant Conjugates ...mentioning
confidence: 99%
“…Antioxidant conjugation of AlNPs can improve their stability and enhance their therapeutic efficacy. Various Al-based NPs exhibited potential antioxidant activity, such as grapefruit peel-fabricated Al 2 O 3 NPs [253], Irganox 1010-fabricated Al 2 O 3 -poly(ethyleneco-butyl acrylate) nanocomposites [254], and Al 2 O 3 NPs synthesized via the laser ablation technique [255]. The conjugation of antioxidants with NPs or entrapped in nanogel can also enhance their bioavailability and facilitate their cellular uptake, in addition to diminishing free radicals [256].…”
Section: Aluminum-based Nps (Alnps) and Their Antioxidant Conjugates ...mentioning
confidence: 99%
“…[25][26][27] It is a ceramic of choice for a wide range of applications in technical fields such as biosensors, catalysts, absorbents, nanoelectronics, optics, etc. [28][29][30][31][32] This work reports an economical and green synthetic method of AlNFs using microwave irradiation that accelerates the kinetics and reduces the temperature required for the reaction. Unlike the temperature used in electrospinning that is above 500 1C, microwave reactions for AlNFs were carried out at 200-240 1C.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that the peels of citrus fruits have been used for the formation of nanoparticles of silver, iron oxide, zirconium, zinc oxide and titanium oxide [14]. Industrially, the plasma discharge method has been employed to prepare these nanoparticles.…”
Section: Introductionmentioning
confidence: 99%